Mitigation of current harmonics in multi-drive system - Thamizh Thentral; Ramya Rathakrishnan; Velu Anbalagan; Karthikeyan Dhandapani; Usha Sengamalai; Palanisamy Ramasamy (Institute of Advanced Engineering and Science, 2022)
Most of the fully automated industries are mainly depending on the single and multi-drive system based on their requirements. In this paper, to investigate the power quality problems in a distributed multi drive system connected to the common uncontrolled rectifier is considered. Uncontrolled rectifier is mainly used as a front-end converter to feed direct current (DC) supply to the same rating of two voltage source inverters with induction motors as a multi-drive system. To analyse the effectiveness of the system the two drive systems are operated in different time period. Then, both are operated simultaneously to monitor the power quality issues, due to the front-end converter present in the system. In both the cases the harmonics in source current is not within the limits of IEEE recommended practices. Therefore, to reduce the harmonic content present in the current at source, a shunt active power filter is implemented. The effect of two drive systems operated at the same time is analysed first. Then, active filter is injected in between the source and the multi-drive system in parallel to improve the power quality of the grid system. The individual and multi-drive drive systems are analysed with the simulation results.